Effects of Sulfur and Nitrogen on Nutrients Uptake of Corn using Acidified Water - Motior Rahman, M.; Soaud, A.A.; Al Darwish, F.H.; Sofian-Azirun, Mohd (Academic Journals, 2011)
A greenhouse experiment was carried out with elemental sulfur (S) and nitrogen (N) fertilizer using acidified water (pH 6.5) to determine nutrients uptake and growth of maize plants grown in calcareous sandy soil. Four levels of elemental sulfur (0, 1, 5 and 10 t ha -1), two levels of N (0 and 0.34 t N ha -1) were tested at Al Foah Agricultural Experiment Farm, United Arab Emirates (UAE) University. In Al Semaih soil, the pH (1.21-1.33) and electrical conductivity (EC) (7.61 dSm -1) decreased by application of elemental S plus N, while EC rose (3.84 dSm -1) and pH reduced (1.20 to 1.11) in Al Zaid soil. Acidity improved by decreasing soil pH, Na and Cl concentration in both soils. A significant change was observed by application of acidified water at Al Semaih soil causing high levels in the initial status of EC, Na and Cl concentrations in the soil. A negative relationship was observed with soil pH among N, P, S, Fe, Zn and Mn, while uptake availability of sulfur and nitrogen had positive relationship with all nutrients. Elemental sulfur at the rate of 5 t ha -1 and nitrogen had a significant contribution towards uptake availability of N, P, S, Fe, Zn and Mn in both Al Zaid and Al Semaih soils. Based on experimental findings, elemental S at the rate of 5 tha -1 and N fertilizer (0.34 t ha -1) is suitable for the growth of maize at both soils. Al Zaid soil possesses advantages over Al Semaih soil due to its high nutrient uptake ability. Â© 2011 Academic Journals.